The HoSTS Project: A Homogeneous Study of Transiting Systems. Issue Volume 8:Issue S299(2013) (6th January 2014) - Chew, Yilen Gómez Maqueo; Faedi, Francesca; Hebb, Leslie; Pollacco, Don; Stassun, Keivan; Cargile, Phillip; Smalley, Barry; Doyle, Amanda; Ghezzi, Luan; Barros, Susana C. C.; Cameron, Andrew Collier
Abstract: The Homogeneous Study of Transiting Systems (HoSTS) will derive a consistent and homogeneous set of both the stellar and planetary physical properties for a large sample of bright transiting planetary systems with confirmed planetary masses and measured radii. Our resulting catalogs of the fundamental properties of these bright planets and their host stars will enable us to explore empirical correlations that will lead to a better understanding of planetary formation and evolution. We present our pilot study of the planet-hosting star WASP-13, and the framework of our project which will allow for the identification of true relationships among the physical properties of the systems from any systematics.